1954
DOI: 10.1103/physrev.94.640
|View full text |Cite
|
Sign up to set email alerts
|

Angular Distribution of Fragments from Neutron-Induced Fission

Abstract: I TW iftwri wtoh to Umm* too peraoaael of Grospo P-1, W-l, aarf P-4 tor toe aae of toot* opotpatoat. to particwlar, w toaak R. R. Potermm of W-l aad R. W. Davto aad A. B. Froatrep of P-4 •or rnwiitarsbia aid to too taetallattoa of oar oppara far aad tor laklac of data. Tbaato are dm* to J. Povelttoa lor too preparation of too ftoatoa foUe. We are tadebted to K. Boyer torq -< toe typo of cnltlamOnr weed to toooo eapertaseato aad to D. L. RU1 tor aeveral latoraottof latorpretattve disrsaelow. ♦♦♦ • • * dp * * • … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
3

Year Published

1954
1954
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 4 publications
0
8
0
3
Order By: Relevance
“…Hill and Wheeler 1 set forth a qualitative picture in a first attempt to explain early experiments on photofission 2 and neutron-induced fission. 3 At the 1955 Geneva Conference Bohr 4 presented a detailed model relating angular distributions of the…”
Section: Introductionmentioning
confidence: 99%
“…Hill and Wheeler 1 set forth a qualitative picture in a first attempt to explain early experiments on photofission 2 and neutron-induced fission. 3 At the 1955 Geneva Conference Bohr 4 presented a detailed model relating angular distributions of the…”
Section: Introductionmentioning
confidence: 99%
“…ZN K e α The results are presented in Fig. 2 along with the experimental values of anisotropy we obtained in [8], and ones measured earlier for energies of up to 20 MeV [20][21][22][23][24][25][26].…”
Section: Resultsmentioning
confidence: 56%
“…It was shown that the model can be used to obtain new information about reactions at intermediate energies and the fission process. 1) from [20], (2) from [21], (3) from [22], (4) from [23], (5) from [24], ( 6) from [25], (7) from [26], and ( 8) from [8]. The dashed, solid, and dotted lines correspond to angular anisotropy calculated with parameters of 22, 17, and 12 keV, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The average error of our measurements for 239 Pu and 237 Np is 1-3%, and for nat Pb -3-14% in the entire investigated neutron energy range. On the same figures for 239 Pu and 237 Np, the results of previous measurements of this anisotropy ( 239 Pu: [10-13, 15-18] and 237 Np: [12,13,15,16,[19][20][21]) included in the EXFOR database are shown. Despite the fact that there are some differences between our data and the results of these earlier works, it can be said that there is generally a satisfactory agreement, especially if we take into account the existing discrepancy between the archival data sets.…”
Section: Resultsmentioning
confidence: 97%
“…Anisotropy of FFs for 237 Np compared with old experimental data from[12,13,15,16,[19][20][21]. Error bars are the statistical errors.…”
mentioning
confidence: 99%